Exploring the cognitive universes of children with special educational needs: perception, understanding, and didactic implications - GHIMPU, Rodica (Acta et Commentationes, Sciences of Education, 2025)
This article examines the unique perspectives of children with special educational needs (SEN) and their potential to positively shape both educational experiences and social interactions. Moving beyond a deficit-focused approach, the study emphasizes the cognitive and emotional strengths of these children, highlighting how they perceive and engage with their environment. The perceptual characteristics of children with autism spectrum disorders, ADHD, and sensory impairments are discussed, along with their influence on the development of empathy, patience, and creativity among their peers. The article also presents practical teaching strategies, such as personalized storytelling, sensory-based activities, and individualized projects, which leverage these differences to transform cognitive diversity into a valuable educational resource. The findings suggest that recognizing and actively incorporating these cognitive differences not only supports children with SEN but also enriches the entire learning community, fostering an inclusive, creative, and empathetic environment.